ANALISIS TANGGUNG JAWAB PEMASOK DALAM PERJANJIAN JUAL BELI TERKAIT CACAT PRODUK (STUDI PADA PT. TOSAMA ABADI) - Rahmawati, Siti Rosy; Artati , Sri Untari Indah (Tribuere, 2024)
The sale and purchase agreement is an integral part of the business transaction regulated in the Civil Code. One of the problems that often occurs is regarding defective products, where the seller is responsible for hidden defects that can cancel the transaction. This study aims to analyze the responsibilities of PT. Tosama Abadi as a supplier in the sale and purchase agreement with PT. Astra Component Indonesia related to product defects. This study uses a normative legal method. The results of the study show that PT. Tosama Abadi has full responsibility for product defects found in auto parts sold to PT. Astra Component Indonesia, as stipulated in the agreement and applicable law. The sale and purchase agreement between PT. Tosama Abadi and PT. Astra Component Indonesia regulates legal relations based on good faith, with the obligations of each party related to the delivery of goods according to specifications, timely payment, and dispute resolution through legal channels if deliberations fail. As a seller and manufacturer, PT. Tosama Abadi is responsible for ensuring the quality, quantity, and delivery of goods according to the agreement, as well as providing a replacement mechanism for production defects and dispute resolution based on applicable legal provisions..